2014
DOI: 10.1590/s0100-204x2014000600006
|View full text |Cite
|
Sign up to set email alerts
|

Produtividade e características biométricas do capim-braquiária em sistema silvipastoril

Abstract: Resumo -O objetivo deste trabalho foi avaliar a produtividade e as características biométricas do capimbraquiária (Urochloa decumbens) sob pastejo, em sistema silvipastoril. Avaliou-se um sistema com árvores nativas de interesse comercial, plantadas em renques, no sentido norte-sul, espaçados por 17 m. Utilizou-se o delineamento experimental de blocos ao acaso, com quatro repetições e parcelas subdivididas, tendo-se avaliado o ciclo de rebrota da forragem nas parcelas, e a distância desta em relação aos renque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
16
0
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 11 publications
3
16
0
5
Order By: Relevance
“…This confirmed the influence of the canopy trees on the interception of incident radiation. Our findings are in line with a study carried out by Pezzopane et al (2015) and Bosi et al (2014) who reported the strong relation between levels of incident solar radiation, and its effect on microclimate, growth characteristics of plants, and soil moisture. The growth of sugarcane was correlated to an increase in k values (Table II), coinciding with an increase in LAI.…”
supporting
confidence: 94%
“…This confirmed the influence of the canopy trees on the interception of incident radiation. Our findings are in line with a study carried out by Pezzopane et al (2015) and Bosi et al (2014) who reported the strong relation between levels of incident solar radiation, and its effect on microclimate, growth characteristics of plants, and soil moisture. The growth of sugarcane was correlated to an increase in k values (Table II), coinciding with an increase in LAI.…”
supporting
confidence: 94%
“…These results followed a similar pattern of response to tiller population and emphasized the negative effect of severe shading on pasture in the SPS, especially in the summer. Decreases in the forage productions in shaded systems were observed by other authors (Bosi, Pezzopane, Sentelhas, Santos, & Nicodemo, 2014;Neel & Belesky, 2017;Santos et al, 2016). The strong restriction of PAR compromises the photosynthetic capacity of the plants, reducing the production of the components of the forage mass (Santiago-Hernández et al, 2016).…”
Section: Discussionmentioning
confidence: 67%
“…The evaluation of dynamic radiation of forestry species and systems is not a widespread practice in scientific circles yet. Another study was carried out by Pezzopane et al (2015) and Bosi et al (2014) who reported on high relation between levels of incident solar radiation, and its effect on microclimate, growth characteristics of plants and soil moisture in areas with high rations During crop cycles, there is an increase in the overall radiation interception, followed by an increase in leaf area index (LAI), but only up to a certain value when full canopy closure is reached, due to leaf self-shadowing (Posada et al, 2012). At this point, the issue of new leaves does not result in an increased amount of light interception.…”
Section: Resultsmentioning
confidence: 99%